2021
DOI: 10.3390/ijerph18052567
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure in the Lombardy Region (Italy) to SARS-CoV-2 Infection: Results from the MUSTANG–OCCUPATION–COVID-19 Study

Abstract: Sero-epidemiological surveys are valuable attempts to estimate the circulation of SARS-CoV-2 in general or selected populations. Within this context, a prospective observational study was conducted to estimate the prevalence and persistence of SARS-CoV-2 antibodies in different categories of workers and factors associated with positivity, through the detection of virus-specific immunoglobulin G and M (IgG/IgM) in serum samples. Enrollees were divided in low exposure and medium-high groups on the basis of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…In particular, Keehner and coll highlighted important differences between the HCW populations and BNT162b2-trial participants, such as the availability of regular testing—irrespectively of symptoms’ occurrence—and the younger age of the HCWs compared with the trial participants [ 1 , 9 ]. It should be also remarked the higher risk of SARS-CoV-2 exposure for hospital workers compared with the general population [ 2 , 3 ]. In addition, it is possible that those individuals with a PCR-positive swab before day 15 may not have already developed an efficacious immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Keehner and coll highlighted important differences between the HCW populations and BNT162b2-trial participants, such as the availability of regular testing—irrespectively of symptoms’ occurrence—and the younger age of the HCWs compared with the trial participants [ 1 , 9 ]. It should be also remarked the higher risk of SARS-CoV-2 exposure for hospital workers compared with the general population [ 2 , 3 ]. In addition, it is possible that those individuals with a PCR-positive swab before day 15 may not have already developed an efficacious immune response.…”
Section: Discussionmentioning
confidence: 99%
“…After a positive assessment of safety and efficacy for BNT162b2 mRNA vaccine granted by different national and international regulatory agencies, a global vaccination campaigns targeted healthcare workers (HCWs) as the first vaccinees, both for ensuring their protection and safety at work, and the sustainability of healthcare systems [ 2 , 3 ]. Growing evidence is emerging about the vaccine response, but data on effectiveness and safety after the second dose deserve careful evaluation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological surveillance has primarily focused on hospitalized patients with severe disease, and, as such, the full spectrum of the disease, including the extent and proportion of mild or asymptomatic infections is less clear. Evidence suggests that asymptomatic or oligo-symptomatic infection is not uncommon (7-10). A recent review reported that at least one third of SARS-CoV-2 infections are asymptomatic and that almost three quarters of persons who are asymptomatic at the time of a positive PCR test result will remain asymptomatic (11).…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…In this frame, a seroprevalence study is an ideal attempt for measuring the true infection rates in general or specific populations (10,14,15) In Italy, a nationwide survey was conducted by the National Institute of Statistics (ISTAT), reporting an IgG seroprevalence of 2.5%. (17).…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…Epidemiological surveillance has primarily focused on hospitalized patients with severe disease, and as such, the full spectrum of the disease, including the extent and proportion of mild or asymptomatic infections, is less clear. Evidence suggests that asymptomatic or oligosymptomatic infection is not uncommon [ 8 - 11 ]. A recent review reported that at least one third of SARS-CoV-2 infections are asymptomatic and that almost three quarters of persons who are asymptomatic at the time of a positive polymerase chain reaction (PCR) test result will remain asymptomatic [ 12 ].…”
Section: Introductionmentioning
confidence: 99%